Controlled synthesis of Co3O4@NiMoO4 core–shell nanorod arrays for efficient water splitting. Issue 35 (9th August 2018) - Du, Xiaoqiang; Li, Nai; Zhang, Xiaoshuang
Abstract : We reported for the first time the development of Co3 O4 @NiMoO4 nanorod arrays on nickel foam (Co3 O4 @NiMoO4 /NF) as a robust Earth-abundant electrocatalyst for water splitting. Abstract : Exploitation of environmentally friendly electrocatalysts for a robust oxygen evolution reaction (OER) in an alkaline medium is very satisfactory. Here, a very low cell voltage of 1.65 V is acquired when Co3 O4 @NiMoO4 /NF is firstly used as a bifunctional water splitting catalyst with 10 mA cm −2 in 1.0 M KOH.